A Survey of Wireless Sensing Security From a Role-Based View - Geng, Ruixu; Wang, Jianyang; Yuan, Yuqin; Zhan, Fengquan; Zhang, Tianyu; Zhang, Rui; Huang, Pengcheng; Zhang, Dongheng; Chen, Jinbo; Hu, Yang; Chen, Yan (IEEE Communications surveys and tutorials, 2025)
Wireless sensing technology has gained widespread adoption, yet its security aspects remain under-explored. This paper presents the first comprehensive survey of wireless sensing security from 2004 to early 2025. We first extend the classical sensing model to build a unified security perspective, which then naturally leads to our main contribution: a role-based classification framework. This straightforward but effective classification organizes research according to whether wireless signals act as Victims of attacks, Weapons for attacks, or Shields for security applications, thus revealing the key relationship between signal physics and security concerns across different technologies. Through a systematic analysis of over 430 publications collected in our open Awesome-WS-Security database, we map the current landscape, identify important challenges such as the complexity of combining physical and digital aspects and the lag in protection mechanisms, and highlight promising future directions including multi-physics modeling, AI-driven intelligent security, and proactive defense strategies. This work provides a foundation for the field, guiding future research and supporting the development of secure wireless sensing systems. Project page:.